Optimizing Human Capital Performance Through Compensation and Work-Life Balance: The Mediating Effect of Motivation at PT. Alam Batu Beach Bungalow - Andiani, Ni Made Nur Ayu; Trianasari, Trianasari; Irwansyah, M. Rudi (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the influence of compensation and work-life balance on employee performance with motivation as a mediating variable at PT Alam Batu Beach Bungalow in Karangasem Regency. The research employs a quantitative method with a path analysis approach. The sampling technique used was total sampling, involving 51 respondents. The results reveal that compensation has a positive and significant effect on both motivation and employee performance. Similarly, work-life balance positively and significantly affects motivation and performance. Furthermore, motivation significantly mediates the effect of compensation and work-life balance on employee performance. These findings indicate that enhancing employee motivation through fair compensation and effective work-life balance contributes to improved performance.